La noción de ‘cauce temporal’ en el surgimiento del valor de ‘pasado cercano’ con la forma verbal he amado - García Fajardo, Josefina (El Colegio de México, 2017)
AbstractReception: July 30, 2016Accepted: January 24, 2017Linguists have already pointed to the central issues in the development of haber in present tense plus participle (Alarcos Llorach 1947; Harris 1982; Arias 2005, among others). I will show here that the notion of “temporal course” (“cauce temporal”: García Fajardo 2014) explains how this construction came to be used to refer to the proximate past. I also intend to show how at a certain time the construction diverged from the “temporal course” and that this divergence coincided with a moment in time —identified by various writers (Lapesa 1942; Lope Blanch 1961, among others)— when the Castilian and the Mexican uses of this construction took separate paths.